Amo Lat: A Sketch of Second Position Discourse Particles in Linawis, the Madridejos Variety of Bantayanon - Baran, Brian Salvador C. (The Archive; Vol 5 No 1 (2024): Regular Issue Vol. 5, No. 1, 2024)
Bantayanon [bfx] is an understudied Central Bisayan language spoken in the Bantayan islands, Cebu (Allen, 2022). This study describes the second position discourse (2P) particles used in one of Bantayanon’s varieties, Linawis which is spoken in the Municipality of Madridejos (Lawís). These particles are found on the second position of a clause and have discourse functions in addition to other grammatical or semantic functions. The 2P particles are analyzed in natural conversation with an eclectic framework that loosely combines ideas from Discourse Functional Linguistics (Du Bois, 2003), Interactional Linguistics (Lindström, 2009), and the Natural Semantic Metalanguage approach (Wierzbicka, 1991). A total of 34 2P particles have been identified thus far. The 2P particles are generally found in the second position of a clause but also sometimes in the post-nominal and terminal positions. They are typically used for aspectual (e.g., transformative na ), temporal (e.g., recent sara ), evidential (e.g., factual baya ), quality and quantity (e.g., restrictive da ), and modal (e.g., mirative ngay-an ) functions. 2P particles, when clustered, follow a weight-based ordering and then a frequency-based ordering within each weight class. Some 2P particles procliticize to the following 2P particles, e.g., assurance gayod becoming g= before the distal prominent adto . Many 2P particles also have allomorphs borrowed from neighboring languages, e.g., the Linawis hypothetical kunta can be interchangeable with Cebuano únta and Hiligaynon táni .